Solving System of Conformable Fractional Differential Equations by Conformable Double Laplace Decomposition Method (Journal of Partial Differential Equations, 2020)
Herein, an approach known as conformable double Laplace decompositionmethod (CDLDM) is suggested for solving system of non-linear conformable fractional differential equations. The devised scheme is the combination of the conformabledouble Laplace transform method (CDLTM) and, the Adomian decomposition method(ADM). Obtained results from mathematical experiments are in full agreement withthe results obtained by other methods. Furthermore, according to the results obtainedwe can conclude that the proposed method is efficient, reliable and easy to be implemented on related many problems in real-life science and engineering.
Keywords: Fractional differential equation; double Laplace transform; Adomian decomposition method; conformable fractional derivative.